Acute Appendicitis Following COVID-19 Infection in Pediatric Patients: A Single Center’s Study in Greece - Christos Kaselas; Maria Florou; Maria Tsopozidi; Ioannis Spyridakis (Diagnostics, 2023)
Purpose: This study investigated the potential association between the previous severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positive infection, as well as vaccination, and the presentation of acute appendicitis in pediatric patients. It has been three years since the World Health Organization (WHO) declared the SARS-CoV-2 pandemic, and city lockdowns and self-protective measures have been applied worldwide. In an effort to contribute to the research on the probable long-term complications of the COVID-19 infection as well as the vaccination against SARS-CoV-2, the current study was designed and investigated patients’ health records in the post-quarantine era. Methods: A retrospective analysis of patients admitted and treated surgically for acute appendicitis from January 2022 to June 2022 was conducted. Demographic and personal data, as well as the COVID-19 infection history of each child, were recorded. The patients who were negative for a previous COVID-19 infection were excluded. For the rest of the sample, the time-to-onset of acute appendicitis, the severity of appendicitis (complicated or uncomplicated), and the vaccination status of the patients were examined. Regarding the time-to-onset of appendicitis, we divided the patients into three groups: group A with a time-to-onset < 3 months, group B with a time-to-onset of 3–6 months, and group C with a time-to-onset of >6 months. Statistical analysis followed and was considered significant if p < 0.05. Results: Sixty-six children with a mean age of 10.5 years (range 1–15 years) were admitted for acute appendicitis during the determined period. After excluding 30 children that were negative for previous COVID-19 infection, we divided the patients into three groups: group A-23 children, group B-7 children, and group C-6 children. A statistically significant incidence of acute appendicitis diagnosis in <3 months after laboratory-confirmed COVID-19 infection (p < 0.01) was found. The incidence of complicated appendicitis was greater in patients with a positive SARS-CoV-2 history, with an estimated odds ratio of 1.8 (p > 0.05). The majority of the children (92%) had not received a COVID-19 vaccination. For the vaccinated children, the relative risk for complicated appendicitis was equal to 1.5 (p > 0.05). Conclusions: The results of our study demonstrate a potential positive relationship between COVID-19 infection and subsequent acute appendicitis in pediatric patients. There are also some speculations on the presentation of complicated cases of appendicitis following COVID-19 infection or vaccination, but these need to be further proven. Further data are required to better understand this potential complication of COVID-19 infection as well as the role of vaccines in the current post-vaccine era.